2010
DOI: 10.1002/em.20635
|View full text |Cite
|
Sign up to set email alerts
|

Tp53 codon‐72 polymorphisms identify different radiation sensitivities to g2‐chromosome breakage in human lymphoblast cells

Abstract: Both the G2 chromosomal radiosensitivity assay and allelic differences in TP53 codon-72 have been associated with cancer predisposition. The relationship between the two endpoints was determined in 56 human EBV-transformed lymphoblastoid cell lines. Although there were overlapping distributions of sensitivity for the different genotypes, cell lines that were homozygous for the proline coding allele were more likely to be resistant to chromatid break formation than those containing two arginine coding alleles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Another study by Alsbeih et al in 2007 also revealed a similar result, namely that the variant TP53 Arg72 allele was associated with a decrease in radiosensitivity [35]. A study by Schwartz et al in 2011 using the human lymphoblast cells revealed that cell lines with homozygous Proline coding allele were more likely to be resistant to radiation-induced chromatid break formation in G 2 chromosomal radiosensitivity assay compared to those containing two arginine coding alleles [36]. Another study by Pereira et al in 2011 revealed that the homozygous arginine coding alleles increase the number of cells with karyorrhexis in buccal cells of head and neck cancer patients after the first session of radiotherapy [37].…”
Section: Association Between Tp53 Arg72pro Polymorphism and Radiosensmentioning
confidence: 87%
“…Another study by Alsbeih et al in 2007 also revealed a similar result, namely that the variant TP53 Arg72 allele was associated with a decrease in radiosensitivity [35]. A study by Schwartz et al in 2011 using the human lymphoblast cells revealed that cell lines with homozygous Proline coding allele were more likely to be resistant to radiation-induced chromatid break formation in G 2 chromosomal radiosensitivity assay compared to those containing two arginine coding alleles [36]. Another study by Pereira et al in 2011 revealed that the homozygous arginine coding alleles increase the number of cells with karyorrhexis in buccal cells of head and neck cancer patients after the first session of radiotherapy [37].…”
Section: Association Between Tp53 Arg72pro Polymorphism and Radiosensmentioning
confidence: 87%
“…Later, Litviakov 33 showed that cancer patients with Pro/Pro genotype have fewer chromatid breaks in comparison to Arg/Pro and Arg/Arg carriers. Moreover, chromosomal radiosensitivity, as measured by the G2-chromosome break assay, has been reported to be associated with polymorphisms in TP53 codon 72 34 . In that study, reduced frequencies of radiation-induced chromatid aberrations were observed in normal human lymphoblast cell lines with the Pro/Pro genotype compared to other genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A common Tp53 polymorphism located at codon 72 (encoding either a proline or arginine residue), within a conserved proline rich SH3 binding domain, is known to be critical for promoting apoptosis [33], [34], and laboratory based studies have demonstrated functional and biologic differences between the two polymorphic forms [35], [36], [37], [38], [39], [40], [41]. The codon 72 polymorphism has a well-characterized geographic distribution, with the frequency of Tp53-72R increasing with geographic distance from the equator.…”
Section: Introductionmentioning
confidence: 99%